Macrofungal diversity in Colombian Amazon forests varies with regions and regimes of disturbance (2012)
ABSTRACT: Here we present the results of fungal biodiversity studies from some selected Colombian Amazon forests in relationship to plant biodiversity and successional stages after slash and burn agriculture. Macrofungal diversity was found to differ between forests occurring in two regions (Araracuara vs Amacayacu) as well as between flooded forests and terra firme forests in the Amacayacu region. Macrofungal biodiversity differed between regeneration states of different age in the Araracuara region. Suitable substrates, especially dead wood that occurred as a result of recent slash and burn agriculture, resulted in the formation of many sporocarps of wood-inhabiting species. Putative ectomycorrhizal species were found in a dipterocarp forest. Fifty two percent of the macrofungal species could not be identified to the species level, but could be assigned to a genus, and it is likely that a significant portion of these represent species new to science. Long term studies are needed to obtain a comprehensive and complete understanding of the diversity and functioning of mycobiota in Amazon forest ecosystems.